Pelatihan Online Membuat Brosur Melalui Imooji untuk Mendukung Promosi UMKM Selama Pandemi Covid-19 - Aditya; Asty Khairi Inayah Syahwani (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Micro, Small and Medium Enterprises (MSMEs) are productive business activities owned byindividuals or individual business entities that contribute to Gross Domestic Product (GDP).Productivity of MSMEs during the pandemic has decreased due to reduced buying power anddecreased demand resulting in decreased business profit. This requires efforts to increase MSMEproductivity through online promotion using brochures (Imooji). Imooji is an online tool that canbe used to create brochures, invitations to events, and product/service catalogs for free. This trainingaims to offer knowledge about the procedures for making digtal brochures to MSMEs during theCovid-19 pandemic. This training activity was held online through the Whatsapp group with 20MSME participants from Bogor. This online training activity is divided into four sessions, the firstsession is of material presentation, the second session is of video screening, the third session is ofdiscussion, and the fourth session is of training evaluation. The impact felt by MSMEs during the Covid-19 pandemic is that people's purchasing power declined by 66.7%, then income decreased by58.3%. The evaluation of this online training activity involved 12 respondents (10 women and 2men). This online training activity was able to increase the knowledge of MSMEs with thepercentage of 66.7% of MSMEs understanding of the training material. This became the basis of theability of MSMEs after the training is carried out in order to make online brochures of products andservices with an attractive appearance.